Pengembangan Assessment dalam Pembelajaran Daring untuk Mata Kuliah Pengukuran dan Instrumen - Kevin Martin; Fivia Eliza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research is motivated by the learning process carried out online because it is not possible to hold a face-to-face learning process or direct learning due to the current Covid-19 epidemic period. Assessment and evaluation of learning in conditions of social distancing and physical distancing can be applied on an online basis which is carried out at home using the remote assessment method. With the rapid development and advancement of technology today, the application of remote assessment is very possible and easier, especially with the existence of the internet network. Therefore, a 4-D development model is used where the results developed are products in the form of essay questions where this is to overcome existing problems so that the learning process can still be carried out. The research objective was to produce a product in the form of essay and oral test questions online on valid measurement courses and instruments. Based on the results of the study using the 4-D model by doing the validity test, it was found that the product in the form of essay questions developed that had been tested got valid results. The validity results were tested by three validators. From the results of the validity test developed, it can be concluded that with the development of the product in the form of the latest essay questions, it can improve the critical thinking ability of each student, and when suddenly there is a quiz given by the lecturer, students will be better prepared to do well and not complain.